Inorganic Nitrate Supplementation in Young and Old Obese Adults Does Not Affect Acute Glucose and Insulin Responses but Lowers Oxidative Stress. Issue 11 (12th October 2016) - Ashor, Ammar W; Chowdhury, Shakir; Oggioni, Clio; Qadir, Othman; Brandt, Kirsten; Ishaq, Abbas; Mathers, John C; Saretzki, Gabriele; Siervo, Mario
Abstract: Background: Aging and obesity are associated with raised oxidative stress and a reduction of nitric oxide (NO) bioavailability, with subsequent decline in insulin sensitivity and endothelial function. Inorganic nitrate is converted into NO via a 2-step reduction process and may be an effective nutritional intervention to modify vascular and metabolic functions. Objectives: This study tested whether inorganic nitrate supplementation improved glucose disposal and attenuated the acute effects of hyperglycemia on oxidative stress, inflammation, and vascular function in young and old obese participants. Methods: Ten young (aged 18–44 y) and 10 old (aged 55–70 y) obese participants consumed 75 g glucose followed by either potassium nitrate (7 mg/kg body weight) or potassium chloride (placebo) in a randomized, double-blind crossover design. Resting blood pressure (BP), endothelial function, and blood biomarkers were measured for 3 h postintervention. Biomarkers included plasma nitrate/nitrite (NOx), glucose, insulin, cyclic GMP, interleukin 6, 3-nitrotyrosine, E- and P-selectins, intercellular adhesion molecule 3 (ICAM-3), and thrombomodulin, as well as superoxide in freshly isolated peripheral blood mononuclear cells (PBMCs). Results: Inorganic nitrate supplementation did not affect plasma glucose ( P = 0.18) or insulin ( P = 0.26) responses. The increase in plasma NOx concentrations 3 h after the administration of inorganic nitrate was significantly higher in young than in old participants (234% increase compared with 149% increase, respectively, P < 0.001). Plasma 3-nitrotyrosine concentrations declined significantly after inorganic nitrate supplementation compared with placebo (3 h postdose, 46% decrease compared with 27% increase, respectively, P = 0.04), and a similar nonsignificant trend was observed for superoxide concentrations (3 h postdose, 16% decrease compared with 23% increase, respectively, P = 0.06). Plasma cyclic GMP, ICAM-3, and thrombomodulin concentrations differed between young and old participants ( P < 0.01). Inorganic nitrate supplementation did not improve BP or endothelial function. Conclusions: Oral supplementation with inorganic nitrate did not improve glucose and insulin responses but reduced oxidative stress in old individuals during acute hyperglycemia. This trial was registered at www.controlled-trials.com as ISRCTN42776917.